Children's incidental social interaction during travel international case studies from Canada, Japan, and Sweden. (July 2017) - Waygood, E.O.D.; Friman, Margareta; Olsson, Lars E.; Taniguchi, Ayako
Abstract: Incidental social interactions such as seeing a known person while travelling are theorized to contribute to community connections and social capital. It is argued in such work that walking may be a critical factor, but the frequency of such interactions is generally unknown. For children, these community connections may increase independent travel and contribute to their well-being. Previous research out of Japan found that walking was indeed more likely to result in children seeing people in general and seeing a known person. However, it is not clear whether that is a culturally anecdotal finding, or whether similar findings would occur in different cultural and transportation contexts. Reasons why it may be anecdotal include: in most cases, all elementary school children walk to school in Japan; many trips occur at a local level and are conducted by non-motorized modes in Japan; greeting others ( aisatsu ) is a cultural value in Japan. This study examines whether one's transport mode relates to having incidental social interaction during their trips for children aged 10–11 in Canada (177), Japan (178), and Sweden (144). Further to previous work, the research carried out here asked the children what type of interaction occurred (spoke, waved, no interaction, or other) which would relate to building or maintaining community connections. The findings demonstrate that the results are internationally applicable and that most incidental social interactions result in a verbal communication in all three countries.